Production of guava [Psidium guajava (L.) Burm.] in the State of Mexico, Mexico - Sangerman-Jarquín Dora Ma.; Larqué Saavedra Bertha Sofia; Navarro Bravo Agustín; Schwentesius de Rindermann, Rita; Damián Huato Miguel Ángel; Cuevas Sánchez Jesús Axayacatl (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of this research was to analyze the technical and socioeconomic aspects of the production of guava in the State of Mexico. The method used was simple, random sampling, conducting open and closed questions to 50 ejido farmers and smallholders in the municipalities of Temascaltepec, and Coatepec de Harinas in 2008. In Temascaltepec average yields were 24.9 t ha-1. For Coatepec de Harinas, the average yield was 28.56 t ha-1. When comparing these yields to the State average and national figures it’s shown that are duplicated, since the State yield is 13.01 t ha-1 and 13.39 t ha-1 nationally. The producers have irrigation and technical assistance in a high percentage (32.2%) compared to the national total, 0.95%. (Díaz, 1987; CONABIO, 2008) despite the high yields, the producers said to have problems in the technology used, as it presents a delay especially in pruning, fertilization, irrigation, harvest schedule, plus the lack of control pests. Regarding the economic gain, the benefit-cost ratio for 2008 indicated that 0.38 of profit is obtained for each product unit sold. A problem that the producers are facing is the fall in real prices between 1980- 2008, these decreased at an average annual rate of -1.24%, has led losses in profitability.